2019
DOI: 10.1111/sms.13545
|View full text |Cite
|
Sign up to set email alerts
|

Inhospital exercise benefits in childhood cancer: A prospective cohort study

Abstract: Childhood cancer patients are at risk of developing important adverse effects, mortality and disease relapse after treatments, which has a substantial economic impact on healthcare systems. The objective of this study was to determine the effects of supervised inhospital exercise on clinical endpoints during childhood cancer treatment.169 children with a new diagnosis of cancer were divided into an exercise intervention (n = 68, 11 ± 4 years) or a control group (n = 101, 11 ± 3 years). The cohort was followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
89
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(98 citation statements)
references
References 24 publications
(42 reference statements)
6
89
0
2
Order By: Relevance
“…In addition, an interesting finding was the lower number of infections after allo-HSCT in the exercise group, which remained quasi-significant after statistical adjustment ( p = 0.023 and 0.083 for total and viral infections, respectively). Further, in concordance with a recent study of our group in which fewer hospitalization days were observed for children and adolescents with cancer undergoing an exercise training program compared with a control group [ 11 ], we observed a trend ( p = 0.052) in unadjusted analysis towards a lower number of days between allo-HSCT and hospital discharge in the exercise group (17 days) compared to the control group (21 days).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, an interesting finding was the lower number of infections after allo-HSCT in the exercise group, which remained quasi-significant after statistical adjustment ( p = 0.023 and 0.083 for total and viral infections, respectively). Further, in concordance with a recent study of our group in which fewer hospitalization days were observed for children and adolescents with cancer undergoing an exercise training program compared with a control group [ 11 ], we observed a trend ( p = 0.052) in unadjusted analysis towards a lower number of days between allo-HSCT and hospital discharge in the exercise group (17 days) compared to the control group (21 days).…”
Section: Discussionsupporting
confidence: 92%
“…The training load was gradually increased depending on the patients’ age, physical capacity, and health status. Exercise intensity was recorded continuously with heart rate (HR) monitors (Xtrainer Plus; Polar Electro OY, Kempele, Finland) and progressively increased from 65% to 80% of HR reserve (i.e., age-predicted maximum HR (220 minus age, in years) minus supine resting HR) [ 11 ]. Thereafter, participants performed strength exercises engaging major muscle groups (leg extension, half squat, plank on knees, supine bridge, arm curl, elbow extension, push-ups, and rowing) for a total duration of ~15 min ( Videos S2 and S3 ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, although LV function did not improve in the present meta-analysis, the fact that exercise interventions attenuated its decline is also worth noting because CCS frequently experience impaired LV function (i. e., LVEF and FS) even after treatment has ended [6]. It should be noted that in the study by Morales et al [8], exercise-associated benefits on LV function were not maintained at 1 year of follow-up or thereafter, suggesting that exercise should be ideally maintained after treatment has ended.…”
Section: Discussionmentioning
confidence: 57%
“…Flow chart of literature search. ▶table Studies analyzing the effects of exercise interventions on CCS during treatment Study Study design Sample size by group (sex), age (mean ± SD; range)Beulertz et al[19] Non-randomized controlled trial -EXP: n = 20 (9 female), 9 ± 5 years (5-13)-CT: n = 13 (8 female), 10 ± 4 years (6-14)-Healthy group: n = 20 (9 female), 9 ± 4 years(5)(6)(7)(8)(9)(10)(11)(12)(13)…”
mentioning
confidence: 99%
“…The effects of the intervention might reduce the children's risk of developing cardiorespiratory fitness-related medical conditions years after their treatment has ended. This is supported by a recent study that showed that exercise during treatment maintained INT the intervention group, CON the control group *The interaction effect in TUG is presented in percentages left ventricular function compared with a non-exercising control group after ended treatment [44]. A key challenge in designing physical activity programs for children with cancer is to accommodate the varying and common treatmentrelated side effects (e.g., nausea, pain, and dizziness).…”
Section: Discussionmentioning
confidence: 71%